Absence of association between whole blood viscosity and delirium after cardiac surgery: a case-controlled study. Issue 1 (December 2016) - CheheiliSobbi, Shokoufeh; van den Boogaard, Mark; Slooter, Arjen; van Swieten, Henry; Ceelen, Linda; Pop, Gheorghe; Abdo, Wilson; Pickkers, Peter
Abstract Background Delirium after cardiothoracic surgery is common and associated with impaired outcomes. Although several mechanisms have been proposed (including changes in cerebral perfusion), the pathophysiology of postoperative delirium remains unclear. Blood viscosity is related to cerebral perfusion and thereby might contribute to the development of delirium after cardiothoracic surgery. The aim of this study was to investigate whether whole blood viscosity differs between cardiothoracic surgery patients with and without delirium. Methods In this observational study postoperative whole blood viscosity of patients that developed delirium (cases) were compared with non-delirious cardiothoracic surgery patients (controls). Cases were matched with the controls, yielding a 1:4 case–control study. Serial hematocrit, fibrinogen, and whole blood viscosity were determined pre-operatively and at each postoperative day. Delirium was assessed using the validated Confusion Assessment Method for the Intensive Care Unit or Delirium Screening Observation scale. Results In total 80 cardiothoracic surgery patients were screened of whom 12 delirious and 48 matched non-delirious patients were included. No significant difference was found between both groups in fibrinogen (p = 0.36), hematocrit (p = 0.23) and the area under curve of the whole blood viscosity between shear rates 0.02 and 50 s-1 (p = 0.80) or between shear rates 0.02 and 5 s-1 (p = 0.78). Conclusion In this case control study in cardiothoracic surgery patients changes in whole blood viscosity were not associated with the development of delirium.